Financial Satisfaction of Students in Semarang State: The Influence of Financial Literacy, Financial Attitudes, and Hedonistic Lifestyles with Financial Technology as a Moderation Variable - Atia Zahro; Dwi Puji Astuti (Jambura Accounting Review, 2026)
This study aims to analyze the influence of financial literacy, financial attitudes, and hedonistic lifestyles on financial satisfaction. Furthermore, financial technology (Fintech) was included in the study as a mediating variable that can strengthen the influence on financial satisfaction. The study participants were students from the Department of Economics at Semarang State University. Probability sampling was conducted using proportional stratified random sampling, with 195 students from the Department of Economics at Semarang State University selected as participants. For this analysis, SmartPLS 4.0 software was used to perform Structural Equation Modeling (SEM-PLS) based on Partial Least Squares (PLS). The results of the study indicate that financial literacy does not have a positive effect on financial satisfaction, whereas financial attitudes, lifestyle, and financial technology have positive effects on financial satisfaction. Regarding moderation effects, the results show that financial technology does not strengthen the influence of financial literacy, financial attitudes, or hedonistic lifestyle on financial satisfaction among students in the Department of Economics at Semarang State University This study contributes to the literature by demonstrating that financial technology serves as a supporting tool, rather than a factor that amplifies the influence of individual financial characteristics on financial satisfaction. In practical terms, these findings suggest that higher education institutions should supplement their financial literacy programs with behavior-based financial education and self-control training to enhance students’ long-term financial well-being.